A powerful high-voltage generator of aperiodic impulses of current of artificial lightning with the peak-temporal parameters rated on an International Standard IEC 62305-1-2010 - M.I. Baranov (National Technical University "Kharkiv Polytechnic Institute", 2015)
Created in accordance with the requirements of international standard of IEC 62305-1-2010 powerful high-voltage generator, forming on the low-resistance actively-inductive loading the aperiodic impulses of current of artificial lightning of the rationed temporal form 10 μs/350 μs and amplitudes of ±(100−200) кА with a foregoing standard by admittances set is presented and described. The results of practical approbation in the laboratory terms of this generator at the in-use electric loading with active resistance of 0.1 Ohm and inductance of 1,5 μH are presented.